Alterações anatômicas da base do crânio nas mielomeningoceles tratadas intra-útero e após o nascimento - Costa, Marcos Devanir Silva Da [UNIFESP] (2019)
Objective: Analyze the skull base of patients that underwent to fetal myelomeningocele repair and compare them to patients submitted to postnatal correction surgery and to a normal control group. Methods: We retrospectively analyzed the records of patients from the Post Natal Group with individuals who underwent myelomeningocele correction surgery up to 48 hours after birth, and the Fetal Group consisting of patients undergoing myelomeningocele correction surgery in the period between 19 and 27 weeks and six days of gestation. We compared birth weight, gestational age at birth, ventriculo-peritoneal shunt placement rate, clivus supraocciput angle (an indirect measure of posterior fossa amplitude), Welcher angle, head circumference adjusted for gestational age at birth up to the age of 2 years. For analysis of the supraocciput clivus angle, we used T1-weighted or T2- weighted brain magnetic resonance in sagittal sections of the postnatal period and a Control Group of individuals which the brain magnetic resonance reveled normal under the age of 5. Results: We selected 70 individuals from the Fetal Group and 68 from the Post Natal Group. A statistically significant difference between the mean supraocciput clivus angle of 87.6o of the Fetal Group was found compared to the mean angle of the of 77.7o of the Post-Natal Group and 89,1o of the Control Group (p <0.0001 in the one-way ANOVA Test). Besides, the mean angle of Welcher in the Fetal Group was 136o , while in the Post Natal Group it was 135o , and 137o in the Control Group, with no statistical difference between the means. Gestational age at birth and sex-adjusted head circumference growth curves were generated and showed that both groups Fetal and Post-Natal had statistically distinct curves, which are within the range of -3 and + 3 score Z of the World Health Organization curves. The comparison of the head circumference growth curves adjusted for sex and gestational age at the birth of the subgroups that used or not acetazolamide in the Fetal Group revealed that patients of both sexes of the group who used the acetazolamide remained tangent to the +3 Score Z while the group that did not use acetazolamide remained between +2 and +3 Score Z. There was 8.5% indication of ventricular-peritoneal shunt or endoscopic third ventriculostomy in the Fetal Group and 76.4% in the Post Natal Group. It was also identified prematurity and low birth weight in the Fetal Group when compared to the Post Natal Group. Conclusion: The increase in the supraocciput clivus angle, which occurs in the intrauterine repaired patients when compared to patients operated after birth, may justify a decrease in the prevalence of hydrocephalus because it represents an increase in the amplitude of the posterior fossa.